A case of double cystic esophageal duplication in VACTERL syndrome: the first case report and a review of the literature - Vasta, G.; Tursini, S.; Rovero, E.; Angotti, R.; Molinaro, F.; Briganti, V. (Frontiers in Pediatrics, 2023)
Background: Esophageal duplication cyst (EDC) is a rare malformation resulting from the embryonic foregut. VACTERL syndrome is a genetical disorder that affects many systems of the human body. We report the first case of VACTERL syndrome associated to asymptomatic double EDC. Case report: A female with ano-rectal malformation and recto-vestibular fistula, kidney malformation and various vertebral defects came to our attention at the time of birth. VACTERL disease was diagnosed. She underwent Peña anoplasty at 4 months of life without complications. MRI was conducted at the age of 2. It accidentally showed a double esophageal duplication (12x35x10 mm) at the level of D7-D9. We planned a thoracoscopy; previous intraoperative esophagogastroduodenoscopy showed an external compression of the native oesophagus. Two duplicated esophageal lesions were removed. The patient made uneventful recovery and was completely asymptomatic at long term follow-up. Conclusions: VACTERL syndrome is still a not well-defined disease. Based on the currently literature this is the first case of a double esophageal duplication in a patient affected by VACTERL syndrome. According to us, thoracoscopic approach of esophageal duplications can be followed by experts. A complete surgical excision is possible even if the cyst shares a common muscular wall with the oesophagus. For this reason, we suggest to close the of muscular wall by simple interrupted suture.